International business and multinational enterprises - Robock, Stefan Hyman (Irwin, 1989)
This book grew out of the authors experience of teaching international business courses in graduate business schools and executive programs around the world since the early 1960's. It is a general introductory text designed for relatively advanced students, with a direct focus on the development of management skills in handling the problems of multinational business.